O doce & o amargo do Secos & Molhados : poesia, estética e política na música popular brasileira - Silva, Vinícius Rangel Bertho da (2007)
This work has the prime objective to analyze the artistic impact provoked by the musical group Secos & Molhados, which original line-up (Gerson Conrad, João Ricardo and Ney Matogrosso) existed between 1971 and 1974. To establish an analysis strategy, it is necessary to take two steps: 1st - To prove that the song lyrics can acquire an aesthetic value as significative as the poetry which belongs to the literary series , restricted to the book s page universe; 2nd - To construct a paradigmatic view above the politic, cultural and aesthetic events of the 50 s, 60 s and 70 s - the Bossa Nova and its disregard by the Brazilian music tradition, the appearance of the Brazilian protest song in a cultural environment taken by debates concerning the ideology of our arts in the presence of the rising of the military regimen, the popular music influenced by the emerging TV industry, the Era of the Festivals and the consequent traditions succeeded from these three musical versants; the hardening of the discussions concerning the musical nationalism and the arisen appearance of Tropicalism; the cultural shock status provoked by the hardening of the military dictatorship since 1968 and the ideological resistance of many of our popular music artists in the middle of the moral and politic repression and the exacerbated nationalism sponsored by the Brazilian officials. Another kind of resources used for the work s analysis is the survey of Secos & Molhados historiography facts so as to explicit the musical and visual impact of its songs and live performances. On the other hand, it is important to investigate how the appearance of this musical phenomenon became possible in terms of mass culture and society of spectacle : the broadcasted popular music, the industrial pomp the growth of the music companies and the consolidation of the record industry in the 60 s. To sum up, the intention of this investigation doesn't abide only in the analysis of the group songs, but in the discussion of the band s anarchic, provocative and highly constructive performance, as it agglutinates different musical and aesthetic tendencies (consecrated author s poems, Kabuki theatre), destroying the frontiers which separate underground from traditional Brazilian Popular Music, conquering at the same time the Rock n Roll consumers and a more intellectualized layer of the Brazilian society.